Experimental stress state-dependent void nucleation behavior for advanced high strength steels. (1st August 2020) - Pathak, N.; Adrien, J.; Butcher, C.; Maire, E.; Worswick, M.
Highlights: Computed tomography is conducted to obtain damage histories for four stress-states: simple shear, uniaxial tension, plane strain tension and equibiaxial tension. The experimental investigation indicated the influence of stress-state on void nucleation behavior. A modified Chu and Needleman's nucleation criterion is proposed by introducing nucleation strain surface as a function of stress-triaxiality and Lode angle parameter. Abstract: The influence of microstructure and stress state, as defined by the stress triaxiality and Lode parameter, on micro-void nucleation was evaluated experimentally for two 800 MPa Advanced High Strength Steels (AHSS), one a Complex-Phase CP800 alloy, with a ferritic-bainitic microstructure, and the other a Dual-Phase DP780 ferritic-martensitic steel. Four plane stress specimen geometries (simple shear, hole tension, v-bend and biaxial Nakazima) were adopted, providing stress triaxiality and Lode parameter values ranging from in-plane shear to biaxial tension under approximately constant stress states until failure. This approach facilitated determination of the relationship between void nucleation and macroscopic stress state. Damage histories were developed from interrupted samples using 3D micro-tomography and quantitative stereology measurement of void nucleation paired with in situ digital image correlation (DIC) strain measurements during the mechanical testing. The trends in damage evolution are strongly linked to the stress state, with very little void nucleation under shear deformation but extensive void damage under biaxial tension for both materials. A dependency of the nucleation rate on Lode parameter was also demonstrated. A higher rate of damage accumulation was observed for the DP780 steel compared to damage in the CP800 steel for all loading conditions highlighting the strong influence of initial microstructure. An analytical framework is proposed to obtain the local stress-state and equivalent plastic strain history from direction integration of the measured DIC strain histories, using a measured hardening law and assumed anisotropic yield function (Yld91) to develop the link between nucleation and the macroscopic stress state. A stress-state dependent nucleation model is proposed by introducing a nucleation strain surface as a function of stress-triaxiality and Lode parameter using a modified form of the strain-based Chu and Needleman nucleation criterion. Graphical abstract: Image, graphical abstract